DESIGN OF A SANDBLASTING WASTE SIEVE MACHINE (CASE STUDY OF SHIPYARD) - Rizal Indrawan; Alfarell Akbar Pradhana Utomo; Ridhani Anita Fajardini; Fipka Bisono; Tri Andi Setiawan; Dhika Aditya Purnomo; Amanda Rosalina; Widya Emilia Primaningtyas (TURBO [Tulisan Riset Berbasis Online], 2025)
At the shipyard, the sandblasting process is routinely carried out to clean material surfaces from rust and other contaminants. This process produces waste in the form of used sand mixed with metal fragments and other debris, requiring separation before the waste can be reused as a concrete mixture. Currently, the separation process is still performed manually, which is considered inefficient due to the large volume of waste, averaging 42 tons per day. To address this issue, the author designed a sandblasting waste sieving machine to make the separation process more automatic and effective. The structural design and strength analysis were carried out using Autodesk Fusion 360 software. The simulation results of the selected design concept showed a minimum safety factor of 6.51, a maximum von Mises stress of 38.134 MPa on the main frame, and a maximum displacement of 0.186 mm on the sieve holder. The design has an estimated total manufacturing cost of Rp4.244.000,-. Â